2020
DOI: 10.3390/ijms21239046
|View full text |Cite
|
Sign up to set email alerts
|

FAHFAs Regulate the Proliferation of C2C12 Myoblasts and Induce a Shift toward a More Oxidative Phenotype in Mouse Skeletal Muscle

Abstract: Branched fatty acid esters of hydroxy fatty acids (FAHFAs) are endogenous lipids reported to have antidiabetic and anti-inflammatory effects. Since skeletal muscle is a major target for insulin, the aim of this study is to explore for the first time the influence of several FAHFAs in C2C12 myoblasts and in skeletal muscle phenotype in mice. Here, we show that eleven FAHFAs belonging to different families inhibit C2C12 myoblast proliferation. In addition, all FAHFAs decreased mitochondrial cytochrome c oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In mice fed with a control diet or supplemented with 9-PAHPA or 9-OAHPA for 12 weeks, both these FAHFAs increased basal metabolism and insulin sensitivity, but without modifying glucose tolerance [13]. Our data also showed that this insulin-sensitive effect was probably exerted at the skeletal muscle level [67]. However, 9-PAHPA intake and to a lesser extent 9-OAHPA intake induced liver steatosis and fibrosis in some healthy mice.…”
Section: Fahfas Improve Glucose Metabolism and Insulin Signallingsupporting
confidence: 55%
See 1 more Smart Citation
“…In mice fed with a control diet or supplemented with 9-PAHPA or 9-OAHPA for 12 weeks, both these FAHFAs increased basal metabolism and insulin sensitivity, but without modifying glucose tolerance [13]. Our data also showed that this insulin-sensitive effect was probably exerted at the skeletal muscle level [67]. However, 9-PAHPA intake and to a lesser extent 9-OAHPA intake induced liver steatosis and fibrosis in some healthy mice.…”
Section: Fahfas Improve Glucose Metabolism and Insulin Signallingsupporting
confidence: 55%
“…To date, as discussed below, the PAHSA family is the most studied. However, the effects of omega-3 fatty acid FAHFAs (DHAHLA and EPAHSA families) [4,32], omega-6 fatty acid derived FAHFAs (several LAHLAs) [66], and two FAHFAs differing only in the length and saturation of the fatty acid chain (9-PAHPA and 9-OAHPA) [12,13,67] were also investigated.…”
Section: Beneficial Effects Of Fahfas In the Obesity-related Metabolic Disordersmentioning
confidence: 99%
“…Recently, an increasing number of FAHFA families and hundreds of regioisomers have been identified in humans, animals, and plants ( 7 , 8 , 9 , 11 ). However, the biological functions of only a few FAHFA family members have been reported ( 7 , 13 , 14 , 16 , 20 , 21 , 22 , 23 , 27 , 37 , 38 , 39 , 40 ). We sought to determine whether different isomers within the same FAHFA family and whether FAHFAs from different families have similar biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…9-PAHPA or 9-OAHPA increased insulin sensitivity, but without modifying glucose tolerance, and increased basal metabolism, both in healthy mice and in obese mice with lower insulin sensitivity (Benlebna et al, 2020a(Benlebna et al, , 2020b. Moreover, 9-PAHPA or 9-OAHPA induced a switch toward a more oxidative contractile phenotype of skeletal muscle, suggesting a muscular origin of the increase in insulin sensitivity observed (Benlebna et al, 2020c). Surprisingly, 9-PAHPA or 9-OAHPA induced hepatic steatosis and fibrosis in some healthy mice but not in obese mice, likely because both FAHFAs had insulinsensitized the healthy liver so much that de novo lipogenesis promoted steatosis/fibrosis (Benlebna et al, 2020a(Benlebna et al, , 2020b.…”
Section: Tissue Content and Biological Functionsmentioning
confidence: 87%
“…Acknowledgement. The authors acknowledge the financial support of the French Lipid Nutrition Group for the work conducted on 9-PAHPA and 9-OAHPA (Benlebna et al, 2020a(Benlebna et al, , 2020b(Benlebna et al, , 2020c. We thank all colleagues who have contributed and/or who are co-authors of our publications cited in this review.…”
mentioning
confidence: 98%